Upgrading pipeline-quality natural gas to liquefied-quality via pressure swing adsorption using MIL-101(Cr) as adsorbent to remove CO2 and H2S from the gas. (1st December 2020) - Rallapalli, Phani Brahma Somayajulu; Cho, Kanghee; Kim, Sun Hyung; Kim, Jong-Nam; Yoon, Hyung Chul
Abstract: We experimentally studied removal of acid gas from natural gas via a pressure swing adsorption (PSA) process that employed a metal–organic framework adsorbent, MIL-101(Cr) to upgrade raw-quality natural gas to liquefied-quality natural gas. We hydrothermally synthesized MIL-101(Cr) in the presence of acetic acid, and then we extrudated it using a 15% carboxymethyl cellulose (CMC) binder. The adsorption isotherms of CO2 and CH4 in the pressure range 0–3 MPa and H2 S in the pressure range 0–0.1 MPa for both powder- and extrudate-form of the MIL-101(Cr) were measured. The CO2 and CH4 adsorption capacities at 3 MPa were found to be 26.31 and 8.89 mmol/g for powder-form and 19.26 mmol/g and 6.04 mmol/g for extrudate-form, respectively. The H2 S adsorption capacities at 0.1 MPa were found to be 7.28 mmol/g for powder-form and 4.04 mmol/g for extrudate-form. Feasibility tests for upgrading 2 vol% CO2 −98 vol% CH4 and 2% CO2 −0.02% H2 S−97.98% CH4 into liquefied-quality natural gas (CO2 < 50 ppm and H2 S < 4 ppm) via PSA were performed under various operating conditions ( e.g., feed gas pressure ( Pfeed ), amounts of purge gas ( Qpurge ), and feed linear velocities ( Vlinear ). In the case of 2 vol% CO2 –98 vol% CH4, the extrudate-form exhibited 1.55 mmol CO2 /g (i.e., 94% of the adsorption capacity at PCO 2 = 0.12 MPa), under the condition of Vlinear = 0.127 m/s, Qpurge = 178.97 cm 3 /g, and Pfeed = 6 MPa. Upgrading 2% CO2 + 0.02% H2 S + 97.98% CH4 via PSA was found to be difficult because of the strong adsorption of H2 S to MIL-101 under the aforementioned conditions.